2006
DOI: 10.1103/physrevb.74.172408
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependent magnetic anisotropy in ultrathinFeCoCu(001)films

Abstract: Using the full potential linearized augmented plane wave method, we have explored the thickness-dependent magnetic anisotropy of ultrathin Fe films with 1 ML Co underlayer on Cu͑001͒ as well as other magnetic properties. It has been found that the magnetic moment of Co underlay is almost intact with increasing Fe film thickness. A similar trend has been observed in interior Fe layers, whereas the surface Fe magnetic moment is greatly enhanced compared to those in other layers. Through magnetic anisotropy calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The tunneling properties and the stability of the magnetic tunneling junctions strongly depend on the structural and magnetic arrangement of the electrodes and barrier material. Several studies demonstrated an influence of nonmagnetic metals (NM) cover layers on the interfacial PMA of Co [10,11,12,13]. It has been recognized, that the effect is determined by the orbital moment anisotropy of Co and could be modified by an interface hybridization of the NM layer (e.g., its d or p orbitals) with Co 3d orbitals [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The tunneling properties and the stability of the magnetic tunneling junctions strongly depend on the structural and magnetic arrangement of the electrodes and barrier material. Several studies demonstrated an influence of nonmagnetic metals (NM) cover layers on the interfacial PMA of Co [10,11,12,13]. It has been recognized, that the effect is determined by the orbital moment anisotropy of Co and could be modified by an interface hybridization of the NM layer (e.g., its d or p orbitals) with Co 3d orbitals [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%